1965
DOI: 10.1136/oem.22.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Organo-Chlorine Insecticide Content of Human Adipose Tissue in South-Eastern England

Abstract: One hundred specimens of human body fat, 50 necropsy and 50 biopsy, were collected in 1964 from a semi-rural area in south-eastern England. The specimens were analysed by two methods and the concentrations of seven organo-chlorine insecticides were determined. The results of the two analytical methods were in good agreement. Endrin and heptachlor epoxide were not detected in any of the specimens analysed for these compounds. The average concentrations of lindane, op'-DDT, and op'-DDE were very small: 0-015 p.p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

1965
1965
1984
1984

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
4
1
Order By: Relevance
“…Maier-Bode (1960) did not detect any differences of storage of DDT and DOE in two groups of patients, divided according to those who died of carcinomas or of other diseases. Robinson et al (1965) and Hofmann et al (1967) reached the same conclusions using a larger sample. In contrast, Casarett et al (1968) found a higher level of DDT, of the two metabolites DOD and DOE, and also of other organochlorine insecticides, in patients who died of carcinomas, but these researchers drew attention to the fact that, in people who lost weight or were cachectic, the amount of insecticide could have been artificially enhanced.…”
Section: Ddt and Related Compoundssupporting
confidence: 67%
See 1 more Smart Citation
“…Maier-Bode (1960) did not detect any differences of storage of DDT and DOE in two groups of patients, divided according to those who died of carcinomas or of other diseases. Robinson et al (1965) and Hofmann et al (1967) reached the same conclusions using a larger sample. In contrast, Casarett et al (1968) found a higher level of DDT, of the two metabolites DOD and DOE, and also of other organochlorine insecticides, in patients who died of carcinomas, but these researchers drew attention to the fact that, in people who lost weight or were cachectic, the amount of insecticide could have been artificially enhanced.…”
Section: Ddt and Related Compoundssupporting
confidence: 67%
“…Robinson et al (1965) did not find any difference between highly and weakly exposed workers to Dieldrin. In the study of Casarett et al (1968), the negative effect observed for DDT was confirmed for Dieldrin and Heptachlor epoxide.…”
Section: Cyclodienes: Aldrin and Dieldrincontrasting
confidence: 45%
“…For dieldrin less extensive surveys have been made, but Table VIII suggests that the residues persisting in human fat are of the same order in both Britain and the United States. Hunter et al (1963) Present paper Hoffman et al (1964) Robinson et al (1965 Mention deserves to be made of the source of the fat samples in the present investigation. With two exceptions the subjects had come to post-mortem examination on the instructions of a coroner.…”
Section: Discussionmentioning
confidence: 99%
“…An official committee, after studying the available evidence, stated (Report, 1964) that, whereas there is no evidence to date that levels of these pesticides hitherto reported in human tissues do any harm or that they present any serious immediate hazard to human beings, the fact that traces of these compounds are found in so many situations is a matter of some concern. The only other surveys of human fat in the U.K. have been confined to south-east England (Hunter et al, 1963 ;Robinson et al, 1965), but in the present study sampling has been extended to other centres in England and Wales, and samples of human breast milk have also been examined. This study was initiated by the Advisory Committee on Pesticides and Other Toxic Chemicals, and was carried out jointly by the Ministry of Health and the Laboratory of the Government Chemist, Ministry of Technology, together with the assistance of a number of forensic pathologists and directors of human breast milk banks.…”
mentioning
confidence: 99%
“…Maier-Bode (1960) did not detect any differences of storage of DDT and DOE in two groups of patients, divided according to those who died of carcinomas or of other diseases. Robinson et al (1965) andHofmann et al (1967) reached the same conclusions using a larger sample. In contrast, Casarett et al (1968) found a higher level of DDT, of the two metabolites DOD and DOE, and also of other organochlorine insecticides, in patients who died of carcinomas, but these researchers drew attention to the fact that, in people who lost weight or were cachectic, the amount of insecticide could have been artificially enhanced.…”
Section: Ddt and Related Compoundsmentioning
confidence: 97%